Pharmacokinetic comparisons of S-oxiracetam and R-oxiracetam in beagle dogs - Wang Wusan; Ji Hui; Li Tingting; Jia Yuanwei; Xie Haitang (Acta Pharmaceutica)
A pharmacokinetic comparison and conformational stability study of S-oxiracetam (S-ORT) and R-oxiracetam (R-ORT) in beagle dogs was used to investigate the possible mechanism of different effects of two oxiracetam enantiomers through a random crossover design. After drug administration to beagle dogs, blood samples were collected at different time points for pharmacokinetic analysis using the UPLC-ESI-MS/MS method. Parts of plasma samples were used for conformation transformation studies using a normal phase high performance liquid chromatographic (NP HPLC) method. The study showed that oxiracetam enantiomers maintained their original conformation when administered orally to beagle dogs. Concentrations of S-ORT were significantly higher than R-ORT 1.5 and 2 h after administration; the AUC0-∞ of S-ORT after oral administration tended to be higher than that of R-ORT, which showed that the different effects between S-ORT and R-ORT may be partly associated with their distinctive absorption at least.